The Approval of Reading Speed Capacities for Laboring Textbooks to Improve Reading Speed for Laboring Textbooks for Students of Vocational Health - Era Yunita Fitria; Wisnu Istanto; Noer Amelia; Merlissa Suemith (Bulletin of Science Education, 2024)
If students are to pursue vocational health or any other technical area of specialization, then they have to acquire effective reading skills. Most learners experience difficulties in speed and comprehension, which impacts negatively on both academic and professional pursuits later in life. This problem is exacerbated by the technical nature of the language used in vocational health education and the bulk of information carried within textbooks, which is imperative in translating classroom knowledge into practice. This study aims to improve the reading speed of labor-intensive textbooks that vocational health students go through, as a professional would face situations in the field where interpreting data speedily is inevitable. While reading speed and comprehension remain critical, remarkably few published studies have covered this topic in vocational health. The present study fills that gap by examining some interventions for improving reading speed for the type of learner under study. This present study employed a mixed-methods approach, which involved gathering both qualitative and quantitative data. For the current study, the participants included 78 vocational health students. An experimental group received targeted speed-reading and comprehension strategies, while the control group followed their normal study routine. Descriptive statistics, T-tests, and correlation analyses were applied to analyze pre-test and post-test data on reading speed and comprehension, together with students' feedback. While the control group indicated very slight improvements, the experimental group showed significant gains in reading speed and comprehension, thus targeted interventions could work well.